Characteristics of Politeness in Language in Perspective, Culture in the Pendopo-Lintang Right Society - Idawati (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe in depth the language politeness in a cultural perspective on the people of the Right Pendopo_Lintang Empat Lawang district in South Sumatra. The focus of the research is the strategy and characteristics of language politeness in a cultural perspective on the people of Empat Lawang district. This research is an ethnographic communication research. Data collection techniques and procedures are carried out by observation, recording, transcripts, and interviews. Verification of data validity is done with credibility, transferability, dependability, and confirmability. Data analysis is done by transcribing recorded data into written form, then analyzed based on situations, events, and communicative actions. Based on the data analysis, it was found that the politeness of the community in the Pendopo-Lintang Kanan district of Empat Lawang had two strategies used in language, namely, positive politeness strategy and negative politeness strategy. Positive politeness strategies are carried out by (1). Condition the attention of listeners, (2). Using greeting, dialect, or slang forms (3). Using jokes (4). Showing optimism, and (5). Involves speakers and speech partners in activities by using the word "we" in communicating. While the negative politeness strategy is used by speakers to reduce the potential for negative faces, it is done by (1). Using indirect speech is intended not to force partners to speak at the request of speakers. (2). Pay homage (3). Apologize (4). Using impersonal forms (5). Declare yourself indebted. Then from the strategy that is reflected in the language politeness, it seems that the characteristics that are characteristic of the politeness of the community language PendopoLintang Kanan district of EmpatLawang substantially include two things: 1). Using sound pressure with a "bee" accent that is intended to make the message easier to understand, but equally important is to maintain the cultural aspects of the local community and 2). Using greetings to the interlocutors who are intended as a form of ta’zim (respect).